Classroom tales : using storytelling to build emotional, social and academic skills across the primary curriculum - Fox Eades, Jennifer M., 1963- (Jessica Kingsley Publishers, 2006)
Jennifer Fox Eades examines the importance of storytelling in the school curriculum and provides a range of tools and techniques to improve self-expression in children.